"The Honest Working Man" and Workers' Control: The Experience of Toronto Skilled Workers, 1860-1892 - Kealey, Gregory S. (Labour / Le Travail, 1976)
Argues that skilled workers in the nineteenth century had more control than was previously realized. Examines three Toronto unions active from the 1860s to the 1890s: the Coopers International Union, Ontario No. 3; the International Typographical Union No. 91; and the Iron Molders International Union No. 28. Analyzes various incidents that demonstrated the power of the skilled workers’ unions. Concludes by discussing the arrival of new threats to workers' control: scientific management, the rise of large corporations, and the expansion of labour-saving machinery.

Essays in Canadian Working Class History - Kealey, Gregory S.; Warrian, Peter (McClelland and Stewart, 1976)
Part of the new aproach currently transforming the writing of Canadian history, this volume approaches the past in terms of people and the activities and events that shaped their existence. The essays explore the roots of the radical tradition and outline the struggle against industrial capitalism between 1850 and 1925. [This book] increases our understanding of the past, provides a valuable perspective on present struggles, and, in a broader sense, contributes substantially to a new and decisive synthesis of Canadian history. –Publisher's description
Keywords: Canada; History; Working class